Testing a context-enriched model of successful aging in multiple large data infrastructures with individuals in advanced old age - Kaspar, Roman; Ehni, Hans-Jörg; Schweda, Mark; Wahl, Hans-Werner (The gerontologist, 2025)
Few people who are ages 80+ meet the criteria of successful aging (SA) proposed by Rowe and Kahn. Going beyond the individual-level conceptualization, we argue that SA always operates in multiple contexts and that context may become most critical in advanced old age. However, we are not aware of any previous study providing an empirical test of how contexts for SA unfold across persons 80 years and older, including those living in institutions.We estimated and compared prevalences of SA based on a classic versus context-enriched understanding of SA in multiple large surveys of older adults, that is, the D80+ study (N = 3.233) and the NRW80+ study (N [baseline] = 1.863). In addition to replication across independent samples, we investigated the stability of context-related SA across time.Prevalences of SA according to Rowe and Kahn were 9.1% in adults aged 80-84 and 0.7% in persons 90 years or older. However, prevalence rates for those with good contexts at their disposal even if not fulfilling Rowe and Kahn’s criteria were much higher across all age groups (80-84 years: 54.9%, 90 years and older: 44.4%). Greater 2-year stability was observed for contextual compared to individual criteria. Notably, positive effects of context on SA were stronger at onset compared to late fourth age.Our findings support a contextualized understanding of SA and inform policy that furthering SA in the fourth age requires the optimization of multiple contexts at the community level.
Veröffentlicht: 16. August 2024
Gesehen am TT.MM.JJJ